Nanoparticles@nanoscale metal-organic framework composites as highly efficient heterogeneous catalysts for size-and shape-selective reactions - Wang, Bingqing; Liu, Wenxian; Zhang, Weina; Liu, Junfeng (Nano research, 2017)
Composites incorporating nanoparticles （NPs） within metal-organic frameworks （MOFs） find applications in many different fields.In particular,using MOF layers as molecular sieves built on the NPs could enable selectivity in heterogeneous catalysis.However,such composites typically exhibit low catalytic efficiency,due to the slow diffusion of the reactants in the long and narrow channels of the MOF shell.In order to improve the catalytic efficiency of these systems,here we report the fabrication of NPs incorporated in nanosized MOFs （NPs@nano-MOFs）,obtained by reducing the size of the MOF crystals grown around the NPs.The crystal size of the composites was controlled by modulating the nucleation rate of the MOFs during the encapsulation of pre-synthesized and catalytically active NPs;in this way,NPs@MOF crystals smaller than 50 nm were synthesized and subsequently used as highly efficient catalysts.Due to the shorter path from the MOF surface to the active sites,the obtained Pt@nano-MOFs composites showed a higher conversion rate than their larger-sized counterparts in the synthesis of imines via cascade reaction of nitrobenzene and in the hydrogenation of olefins,while retaining the excellent size and shape selectivity associated with the molecular sieving effect of the MOF layer.The present strategy can also be applied to prepare other encapsulated nanostructures combining various types of NPs and nano-MOFs,thus highlighting the broad potential of this approach for developing optimized catalysts with high reactivity and selectivity.